Science, technology, agri-food systems, health, and wellbeing: logic, dynamics, and relationships - Vargas-Canales, Juan Manuel; Orozco-Cirilo, Sergio; Estrada, Salvador; del Carpio-Ovando, Perla Shiomara; Camacho-Vera, Joaquín Huitzilihuitl; López-Carmona, Daniela; García-Melchor, Nicasio; Rodríguez-Haros, Benito; Valdés-Cobos, Alberto; Sánchez-Torres, Yolanda; Fresnedo-Ramírez, Jonathan; Palacios-Rangel, María Isabel; et al. (Frontiers in Sustainable Food Systems, 2024)
The agri-food sector worldwide is the most important for life. The recent pandemic made it clear that the best way to resist, overcome and adapt to health problems is by maintaining a healthy, adequate and balanced diet. The problem is that currently food comes from an agri-food sector subordinated to an economic and scientific model. In this sense, the objective of this work was to carry out an analysis of the logic, dynamics and relationship between science, technology, agri-food systems, health and well-being. As a first point, an exploration of the evolution and trends of science and technology in the agri-food sector is carried out. Next, an analysis is developed on the importance of agri-food systems and the ways in which they have been configured. Subsequently, the relationship between food and health and the main implications and damage caused by the current agri-food regime are addressed. Based on the above, some alternatives are proposed to improve nutrition, health and well-being. These alternatives imply, on the one hand, a profound reconfiguration of technological systems, orienting them towards the reproduction of life. Secondly, and as a consequence of the above, a reorganization of the economic and social systems. To achieve this, it is advisable to design a policy that promotes sustainable agri-food systems and integrate broad work and research groups that allow addressing these problems and proposing alternatives from different perspectives. Subsequently, define divulgation programs on current problems and scientific and technological advances with the aim of having a true impact on society and genuine social appropriation of knowledge.